Keterkaitan Indeks Massa Tubuh dan Kelelahan Kerja dengan Stres Kerja pada Pekerja Lapangan PT X - Wijayanti, Reni; Wardani, Tyas Lilia; Widjanarti, Maria Paskanita (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
The increasing workload and productivity demands in the industrial sector have significantly impacted the physical and mental health of workers, particularly field workers who face considerable challenges daily. These field workers, who frequently encounter various physical and mental challenges, are at a higher risk of experiencing health issues, including job-related stress. This study aims to explore the relationship between Body Mass Index (BMI) and work fatigue with the level of job stress among field workers at PT X. The research design employed is an analytical observational study with a Cross-Sectional approach. A total of 151 field workers at PT X were selected as the sample using a total sampling technique. The research utilized the Fatigue Assessment Scale (FAS) questionnaire to assess work fatigue, the workplace stress place questionnaire to measure job stress levels, and height and weight data to calculate the respondents' Body Mass Index (BMI). Data analysis was conducted using Spearman's rank correlation test. The results indicate a moderately strong positive correlation between BMI and job stress, with a Spearman correlation coefficient of 0.487 (p < 0.001). Furthermore, a strong positive correlation was also found between work fatigue and job stress, with a correlation coefficient of 0.529 (p < 0.001). These findings suggest that increases in BMI and work fatigue are associated with higher levels of job stress.